A Goose is a Goose? Identifying Differences Between Migratory and Resident Canada Geese (Rutgers Cooperative Extension, NJ Agricultural Experiment Station, 2003)
This fact sheet provides information on the identification of migratory and resident Canada geese as well as differences in behavior, habitat, diet, and nesting. Information on the regulatory status of Canada geese is also included.